2021
DOI: 10.1029/2020jd034327
|View full text |Cite
|
Sign up to set email alerts
|

Growing Atmospheric Emissions of Sulfuryl Fluoride

Abstract: The potent greenhouse gas sulfuryl fluoride (SO2F2) is increasingly used as a fumigant, replacing methyl bromide, whose structural and soil fumigation uses have been phased out under the Montreal Protocol. We use measurements on archived air samples and in situ observations from the Advanced Global Atmospheric Gases Experiment (AGAGE) and a box model of the global atmosphere to show a global increase of SO2F2 mole fraction from 0.3 ± 0.02 to 2.5 ± 0.08 ppt along with a global increase in emissions from 0.5 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…22 However, the use of a greenhouse gas SO 2 F 2 is not safe as it may leak out in operation. 23 Although the organoselenium-catalyzed dehydration of aldoximes can produce nitriles under environment friendly conditions, it required for hours up to days. 24 To some extends, those disadvantages restrict its wide applications.…”
mentioning
confidence: 99%
“…22 However, the use of a greenhouse gas SO 2 F 2 is not safe as it may leak out in operation. 23 Although the organoselenium-catalyzed dehydration of aldoximes can produce nitriles under environment friendly conditions, it required for hours up to days. 24 To some extends, those disadvantages restrict its wide applications.…”
mentioning
confidence: 99%
“…SO 2 F 2 is neurotoxic and therefore poses a major hazard to humans, e.g., to inhabitants of treated houses or workers in the logistics industry, with an occupational exposure limit (OEL) of 5 ppm and an immediate danger for life and health starting from 200 ppm [ 2 ]. Since the adoption of the Montreal Protocol in 1987, in which the use of methyl bromide as a fumigant was phased out because of its harm to the ozone layer, SO 2 F 2 has largely replaced methyl bromide, and the amount used drastically increased to more than 2000 metric tons per year [ 3 , 4 ]. Apart from its toxicity, SO 2 F 2 is a potent greenhouse gas with a global warming potential of 4780 and an atmospheric lifetime of 36 years [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, scientists have found that SO 2 F 2 has a high global warming potential of approximately 4780 and an atmospheric lifetime of 100 years 6 (similar to that of CO 2 ), and its global use has caused environmental problems. 7 The lifetime of sulfuryl fluoride emitted into the atmosphere after fumigation treatment has been reported to be 4.5 years, 8 and it is likely to increase with future use. In addition, SO 2 F 2 is regarded as an inhalation hazard, 9 and prolonged exposure can cause harm to the central nervous system and respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…It has replaced CH 3 Br, which was phased out under the Montreal Protocol, 5 owing to its advantages of not destroying the ozone layer and zero ozone‐depleting potential value. However, scientists have found that SO 2 F 2 has a high global warming potential of approximately 4780 and an atmospheric lifetime of 100 years 6 (similar to that of CO 2 ), and its global use has caused environmental problems 7 . The lifetime of sulfuryl fluoride emitted into the atmosphere after fumigation treatment has been reported to be 4.5 years, 8 and it is likely to increase with future use.…”
Section: Introductionmentioning
confidence: 99%